Shooting fish in a barrel? Assessing fisher‐driven changes in catchability within tropical tuna purse seine fleets. Issue 5 (23rd February 2017) - Tidd, Alex; Brouwer, Stephen; Pilling, Graham
Abstract: With constant innovation to find more efficient ways to find, catch and process fish, catchability in wild fisheries can increase. Catchability is a combination of resource abundance, fishing effort and fishing efficiency: any increase in fleet efficiency can lead to undesirable effects not only on stocks, but also on the ability to assess them. When using effort controls as part of management, it is necessary to adjust for the increase in catchability due to the increases in efficiency over time to avoid stock depletion. Accounting for changes in catchability can be problematic for pelagic stocks, due to the changes in fishing behaviour and the continual change in fishing efficiency. This study investigates the success in finding patches of fish for fleets operating within the western and central Pacific purse seine fishery between 1993 and 2012. Three indices, widely used in ecological research, were used to study how spatial variation in fisher behaviour for sets on fish aggregating devices (FADs) and free‐school sets was related to catchability. For free‐school set types, the diversity index was negatively correlated with Katsuwonus pelamis catchability. When this index was low, catch rates were at their highest and there was a reduction in the area fished. In contrast, for FAD sets, catches increase when the patchiness index was low, implying a degree of random behaviour, potentially due to advances in FAD technology. An improved understanding of the spatial allocation of effort can improve catchability estimates widely used for fisheries stock assessments and in indices of global biodiversity.